Pengaruh Pemberian Jus Jeruk (Citrus) Terhadap Penurunan Tekanan Darah Pada Lansia Dengan Hipertensi - Evayanti, Lely; Amirus, Khoidar; Maternity, Dainty (ANJANI Journal (Medical Science & Healthcare Studies), 2024)
Background: Hypertension occurs in the age group of 31-44 years (31.6%), ages 45-54 years (45.3%), ages 55-64 years (55.2%). From the prevalence of hypertension of 34.1% it is known that 8.8% are diagnosed with hypertension and 13.3% of people diagnosed with hypertension do not take medication and 32.3% do not regularly take medication. One herbal treatment using citrus juice (Citrus sinensis) Orange juice is also considered a good source of essential nutrients such as vitamin C, folate, and potassium. Vitamin C has recently been found to protect endothelial and LDL cells from intra-oxidative stress and extracellular.Pourpuse: To know the effect of citrus juice on blood pressure reduction in seniors with hyperthesis at UPTD Inpatient Health Center Able Poned Totomulyo.Methods: Types of quantitative research, research design methods (quasi experimental) with post pretes approach with control group Population in this study are 30 seniors with hypertension, sampling techniques using purposive samplin, univariate data analysis and bivariate using t-tests.Result: The average systolic blood pressure after intervention was 130.67 While diastolic blood pressure after intervention was 99.33, a group that was not given orange juice from 15 study respondents, achieved a mean score or average blood pressure score after intervention of 137.67 diastolic blood pressure after intervention of 107.33. T test obtained p value 0,000 < α (0.05) means H0 is rejected and Ha is accepted.Conclusion: there were effect of citrus juice on the decrease in blood pressure in the elderly with hyperthesis in uptd Inpatient Health Center Able Poned Totomulyo.Suggestion: As an information material for health workers to give orange juice for 7 days with a dose of 500 ml 1 day once to the elderly who have high blood pressure. Keywords: Citrus Juice, Blood Pressure, Elderly ABSTRAKLatar Belakang: Hipertensi terjadi pada kelompok umur 31-44 tahun (31,6%), umur 45-54 tahun (45,3%), umur 55-64 tahun (55,2%). Dari prevalensi hipertensi sebesar 34,1%  diketahui bahwa sebesar  8,8% terdiagnosis hipertensi dan 13,3% orang yang terdiagnosis hipertensi tidak minum obat serta 32,3% tidak rutin minum obat. Salah satu pengobatan herbal menggunakan jus jeruk (Citrus sinensis) Jus jeruk  juga dianggap sebagai sumber yang baik dari nutrisi penting seperti vitamin C, folat, dan potasium. Vitamin C baru-baru ini telah ditemukan untuk melindungi sel-sel endotel dan LDL dari stres oksidatif intra dan ekstraseluler.Tujuan: Mengetahui pengaruh pemberian jus jeruk (citrus) terhadap penurunan tekanan darah pada lansia dengan hipertesni di UPTD Puskesmas Rawat Inap Mampu Poned Totomulyo.Metode: Jenis penelitian kuantitatif, desain penelitian metode (quasi eksperiment) dengan pendekatan pretes post with control group Populasi dalam penelitian ini adalah 30  lansia dengan hipertensi, teknik sampling menggunakan purposive sampling, analisa data univariat dan bivariat menggunakan t-tes.Hasil: Rata-rata tekanan darah sistolik setelah intervensi sebesar 130,67. Sedangkan tekanan darah diastolik setelah intervensi sebesar 99,33,  kelompok yang tidak diberi jus jeruk dari 15 responden penelitian, diperoleh hasil nilai mean atau nilai rata-rata tekanan darah setelah intervensi sebesar 137.67 tekanan darah diastolik setelah intervensi sebesar 107.33. uji t didapat p value 0,000 < α (0,05) artinya H0 ditolak dan Ha diterima.Kesimpulan: Terdapat pengaruh pemberian jus jeruk (citrus) terhadap penurunan tekanan darah pada lansia dengan hipertesni di UPTD Puskesmas Rawat Inap Mampu Poned Totomulyo.Saran: Sebagai bahan informasi bagi tenaga kesehatan agar memberikan jus jeruk selama 7 hari dengan dosis 500 ml 1 hari satu kalikepada lansia yang mengalami tekanan darah tinggi. Kata Kunci: Jus Jeruk (citrus), Tekanan Darah, Lansia